Hierarchically assembled helicates as reaction platform – from stoichiometric Diels–Alder reactions to enamine catalysis - Van Craen, David; Begall, Jenny; Großkurth, Johannes; Himmel, Leonard; Linnenberg, Oliver; Isaak, Elisabeth; Albrecht, Markus (Beilstein Journal of Organic Chemistry, 2020)
The stereoselectivity of a Diels–Alder reaction within the periphery of hierarchically assembled titanium(IV) helicates formed from mixtures of achiral, reactive and chiral, unreactive ligands was investigated in detail. Following the pathway of the chiral induction, the chiral ligands, solvents as well as substituents at the dienophile were carefully varied. Based on the results of the stoichiometric reaction, a secondary amine-catalyzed nitro-Michael reaction is performed as well which afforded reasonable diastereoselectivities.
Keywords: Diels–Alder reaction; enamine catalysis; hierarchical helicates; remote-control; stereoselectivity